(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Homicide is a legal term for any killing of a human being as a result of the conduct of another. There has been a global increase in homicide and it causes over 500,000 deaths per year worldwide. Throughout the world deaths due to firearm weapons have been increased tremendously. Depending on the circumstances of the death, homicides can be divided into murder, manslaughter, justifiable homicide, killing in war, euthanasia and execution. Objectives: To find out socio-demographic features of homicidal deaths in some part of Dhaka city. Materials and Methods: A record based cross-sectional study includes 506 cases of homicide out of the total of 3005 medico-legal autopsies conducted at Forensic Medicine Department of Dhaka Medical College during the year of March 2006 to February 2007. Data were collected using a pre-designed schedule from Post mortem registers and reports. The cases have been labeled as homicide on the basis of autopsy and police inquest report. All the data were collected in a predefined data collection sheet and necessary statistical analyses were performed by using SPSS (Statistical Package for Social Science) software. Results: A total number of 3005 medico-legal autopsies were conducted, of them 1594 (53.04%) cases were accidents, 786 (26.15%) cases were suicide, 506 (16.84%) cases were homicide, undetermined cases were 88 (2.93%) and 31 (1.04%) cases were natural deaths. Of them 190 (37.55%) were caused by firearms. Other methods used for homicide were 97 (19.17%) cases by blunt weapons, 82 (16.21%) by sharp cutting weapons, 49 (9.68%) by stab injuries. Most of the victims 188 (37.15) were in the age group of 21-30 years followed by 110 (21.74%) in the age group of 31-40 years. In 447 (88.33%) cases the victims were male and 480 (94.86%) were Muslims. Conclusion: Homicide is a relatively rare offence than accidents or suicides but it is one of the most notifiable crimes in country as they are widely publicized by the media due to their severity and visibility. Homicidal deaths, mostly due to fire arms have increased substantially in the last decade. Strict measures should be taken to monitor and control the possession of illegal fire arms. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 30-33